Distinct mechanisms contribute to immunity in the lantibiotic NAI‐107 producer strain Microbispora ATCC PTA‐5024. (25th June 2015) - Pozzi, Roberta; Coles, Murray; Linke, Dirk; Kulik, Andreas; Nega, Mulugeta; Wohlleben, Wolfgang; Stegmann, Evi
Abstract: The investigation of self‐resistance in antibiotic producers is important to understand the emergence of antibiotic resistance in pathogens and to improve antibiotic production. Lantibiotics are ribosomally synthesized antibiotics that mostly target peptidoglycan biosynthesis. The actinomycete M icrobispora  ATCC PTA‐5024 produces the lantibiotic NAI‐107, which interferes with peptidoglycan biosynthesis by binding bactoprenol‐pyrophosphate‐coupled peptidoglycan precursors. In order to understand how M icrobispora counteracts the action of its own antibiotic, its peptidoglycan composition was analysed in detail. M icrobispora peptidoglycan consists of muropeptides with D‐Ala and Gly in similar proportion at the fourth position of the peptide stems and alternative 3‐3 cross‐links besides the classical 4‐3 cross‐links. In addition, the NAI‐107 biosynthetic gene cluster ( mlb ) was analysed for the expression of immunity proteins. We show that distinct immunity determinants are encoded in the mlb cluster: the ABC transporter MlbYZ acting cooperatively with the transmembrane protein MlbJ and the lipoprotein MlbQ. NMR structural analysis of MlbQ revealed a hydrophobic surface patch, which is proposed to bind the cognate lantibiotic. This study demonstrates that immunity in M icrobispora is not only based on one determinant but on the action of the distinct immunity proteins MlbQ, MlbYZ and MlbJ.